(untitled) (Research, Society and Development, 2022)
The degradation of buildings, inevitable due to the aging of construction materials, acquires greater relevance when it involves the theme of cultural heritage. The facade cladding works as a layer of protection, however, due to its exposure to environmental and climatic conditions, it becomes the area with the highest incidence of damage in the building. For the control of these damages, and studies of how to carry out an adequate maintenance, the detection of pathological manifestations in the facades must be accomplished, starting from a visuospatial inspection, of the metric and/or photographic type. More recently, with the increasing accessibility of digital technologies, methods such as photogrammetric and laser scanning have emerged. This type of study, the detection of pathological manifestations, particularly when dealing with a built cultural heritage, is a complex task, since only non-destructive processes must be performed. This work presents advantages and disadvantages of five different methods, based on several authors, associated to the evaluation of the state of degradation of mortar facades. The results, systematized in tables and graphs, indicate that there is no perfect technique, but combining several of them can lead to excellent results. It was also observed that the results obtained by different researchers, to estimate the damage caused to the coating, are conditioned to their technical knowledge and the infrastructure available for the interpretation of the data.